Study on major legal issues and solutions in pandemic treaty negotiations - Chen, Weiqi (Frontiers in Public Health, 2024)
The COVID-19 pandemic has triggered a reflection on the deficit of global health governance, and it is urgent to strengthen cooperation among countries through international law. Although there is already a PHEIC system to deal with sudden public health events such as pandemics, the system is not enough to deal with a global pandemic, and WHO and its member states are conducting pandemic treaty negotiations in stages. The draft WHO Pandemic Agreement reflects the negotiating process until 24 May 2024. The negotiating team is faced with legal issues such as the treatment of the relationship between the pandemic treaty and the International Health Regulations, the determination of the contracting model, the attribution of the pandemic definition power and the construction of the dispute settlement mechanism. In order to solve the above problems, we should distinguish the functions of the pandemic treaty and the International Health Regulations, adopt both hard and soft contracting model, establish an open and transparent pandemic determination mechanism, reform the institutional functions of WHO, and establish an effective dispute settlement mechanism. Key words: International health rule of law; Pandemic Treaty; The novel coronavirus; A community of human health; International Health Regulations 2005 1.IntroductionThe draft WHO Pandemic Agreement reflects the negotiating process until 24 May 2024. A preliminary draft of 37 articles focused on the use of terminology, the principle of objectives, pandemic prevention and public health surveillance, a "One health" approach to prevention, preparedness and response to pandemics, preparedness and resilience of health systems was formed. Member States have reached preliminary agreement on some of the chapters, there is initial convergence on some elements, and there are many texts where there is no convergence and where there is disagreement. The draft is more like a partial complement to the missing